Model for Estimating Domestic Outdoor Water Demand of Properties in Residential Estates - Plessis, J.L. du; Jacobs, H.E. (Procedia engineering, 2014)
The outdoor water consumption of residential properties is a major contributor to the seasonal fluctuation of water demand. An outdoor water demand estimation model is presented where water-use components were mathematically defined and combined to develop an outdoor water demand model. The model input parameters were formulated from data available for enclosed residential estates, where conditions such as types of vegetation, irrigated area and size of pool could be prescribed in a constitution, usually instituted by a home owners association in South Africa. This study leads the way to further research into end-use modelling of outdoor water demand.